Facial Atrophy in Oral Submucous Fibrosis: An Association or a Coincidence - Sameep S. Shetty; Premalatha Shetty; Amruta Ramgonda Chougule (Case Reports in Dentistry)
The anecdotal clinical presentation of OSMF that includes vesicle formation, burning sensation, intolerance to hot and spicy food, and trismus due to circumoral fibrous bands has been ringing in our ears for decades but the current paper flags novelty by portraying a rare presentation of an advanced stage of OSMF.